Regulatory T cell function in autoimmune disease - Rajendiran, Anandhi; Tenbrock, Klaus (Journal of translational autoimmunity (Online), 2021)
Autoimmune diseases are characterized by a failure of tolerance to own body components resulting in tissue damage. Regulatory T cells are gatekeepers of tolerance. This review focusses on the function and pathophysiology of regulatory T cells in the context of autoimmune diseases including rheumatoid and juvenile idiopathic arthritis as well as systemic lupus erythematosus with an overview over current and future therapeutic options to boost Treg function. •Regulatory T cells are critical mediators of immune tolerance and critically depend on external IL-2.•Tregs are expanded during inflammation, where the local milieu enhances resistance to suppression in T effector cells.•Human Tregs are characterized by different markers, which hampers the comparability of studies in patients with autoimmunity.